Comparison of stone clearance rate and need of nephrostomy in conventional versus mini percutaneous nephrolithotomy. - Muhammad Jafar; Syed Wajid Ali; Khalid , Sana (International Journal of Endorsing Health Science Research, 2022)
Background: The increased renal stone size affects the stone clearance rate and the need for nephrostomy in (Percutaneous nephrolithotomy) PCNL. Also, complete stone clearance of bulky renal calculi causes blood loss during PCNL, resulting in hemoglobin drop and sometimes requiring transfusion. This is a frequently encountered phenomenon and is quite problematic for urologists and patients. This study aimed to determine the rate of stone clearance and nephrostomy needed in Mini-PCNL over Conventional PCNL. Methodology: A comparative study was conducted at the urology department of PIMS, Islamabad. A total of eighty (n=80) adult patients of either gender between ages 18-65 years were enrolled. Subjects enrolled had radiographic evidence of renal stones of > 1cm. Group A patients underwent conventional PCNL procedures, and Group B patients underwent Mini PNCL. The rates of stone clearance nephrostomy needed were compared between the two study groups. Results: The mean age of study participants in group A was (33.7 ± 12.1) and in group B (36.5 ± 11.1). The mean sizes of the stone were 2.4 cm and 2.7 cm in groups A and B, respectively. X-rays were used to assess the stone clearance rate on the first operative day in both study groups. Stones were cleared in group-A at 87.5% (n=35) and in group B at 82.5% (n=33). Nephrostomy was needed in group A at 50.0% (n=20) and in group B at 47.5% (n=19). Conclusion: The stone clearance rate and the need for a nephrostomy tube were nearly similar in both intervention groups.